EndoClot Polysaccharide Hemostatic System in Nonvariceal Gastrointestinal Bleeding: Results of a Prospective Multicenter Observational Pilot Study. Issue 10 (November 2016) - Preiß, Jan C.; Barmeyer, Christian; Bürgel, Nataly; Daum, Severin; Epple, Hans-Jörg; Günther, Ute; Maul, Jochen; Siegmund, Britta; Schumann, Michael; Tröger, Hanno; Stroux, Andrea; Adler, Andreas; et al.
Abstract : Background and Study Aims: Hemostatic powders have been introduced to improve the management of gastrointestinal (GI) bleeding and to extend the variety of tools available for emergency endoscopy. The aim of the present pilot study was to evaluate the indication profiles and the short-term outcome of EndoClot. Patients, Materials and Methods: In a prospective observational pilot study patients with acute nonvariceal GI bleeding were included. Primary or secondary application of EndoClot was assessed. Hemoglobin, prothrombine time and platelets were documented before and after hemostasis. The efficacy of EndoClot was assessed 72 hours and 1 week after application. Results: Seventy patients with acute GI bleeding were recruited into the study. Eighty-three percent (58/70) of the patients had upper and 17% (12/70) had lower GI bleeding. In the upper GI tract treatment success was achieved in 64% (30/47, 95% confidence interval, 50%-76%) after primary use and in all patients, when used after established techniques had failed (95% confidence interval, 70%-100%). In lower GI bleeding hemostasis was achieved in 83% of cases (10/12, 95% confidence interval 54%-97%). Rebleeding occurred in 11% (8/70), in 10% EndoClot served as a bridge to surgery (7/70). Conclusions: EndoClot expanded the therapeutic options in the management of GI bleeding. It was applicable as a monotherapy or in combination with other techniques from oozing bleeding type or lower. It was most effective in diffuse or extensive bleeding activity or when access to the bleeding vessel was difficult. EndoClot can be applied as a bridge to surgery when classical methods of hemostasis have failed.